Optimal strategy selection approach of moving target defense based on Markov time game - Jinglei TAN; Hengwei ZHANG; Hongqi ZHANG; Hui JIN; Cheng LEI (Tongxin xuebao)
For the problem that the existed game model was challenging to model the dynamic continuous characteristics of network attack and defense confrontation effectively,a method based on Markov time game was proposed to select the optimal strategy for moving target defense.Based on the analysis of the attack and defense confrontation process of moving targets,the set of moving target attack and defense strategies was constructed.The dynamics of the single-stage moving target defense process was described by time game.The randomness of multi-stage moving target defense state transformation was described by Markov decision process.At the same time,by abstracting the use of resource vulnerability by attack-defense participants as the alternation of the control of the attack surface,the versatility of the game model was effectively guaranteed.On this basis,the existence of equilibrium was analyzed and proved,and the optimal strategy selection algorithm was designed.Finally,the practicality of the constructed model and the effectiveness of the algorithm are verified by an application example.